Pengaruh Strategi Bisnis Asset-Light Terhadap Net Profit Margin - nazma awwaliyah khonitatillah; Achmad Zaki; Cynthia Eka Violita; M Mustaqim (Forum Kerjasama Pendidikan Tinggi, 2026)
The shift in the global economic structure towards the digital era encourages companies to improve operational efficiency through the implementation of asset-light business strategies. This study aims to analyze the effect of asset-light business strategies proxied by Sales to Net Fixed Assets (SNA), Total Asset Turnover (TATO), Capital Expenditure (CAPEX), and Intangible Asset Ratio (RATB) on Net Profit Margin (NPM) in companies included in the IDX30 index for the 2022–2024 period. The study uses a quantitative approach with an associative-causal design. The sample was selected using a purposive sampling technique, resulting in 24 companies with a total of 72 observational data. Data analysis was performed using multiple linear regression with SPSS 27. The results showed that the SNA variable has a positive and significant effect on NPM with a regression coefficient value of 0.478, a t-value of 4.859, and a significance level of 0.000. The TATO variable has a negative and significant effect on NPM with a regression coefficient of -0.188, a t value of -2.144, and a significance of 0.036. The CAPEX variable has a positive and significant effect on NPM with a regression coefficient of 0.267, a t value of 4.977, and a significance of 0.000. Meanwhile, RATB has no significant effect on NPM with a regression coefficient of -0.023, a t value of -0.456, and a significance of 0.650. The Adjusted R Square value of 0.360 indicates that 36.0% of the variation in NPM can be explained by the four independent variables in this study, while the remaining 64.0% is influenced by other factors outside the research model. This finding indicates that efficient management of fixed assets and appropriate capital investment can increase company profitability, while high asset turnover and ownership of intangible assets are not necessarily able to increase net profit margins.